2020
DOI: 10.1002/hed.26160
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcoma of oral cavity: Systematic review of cases reported to date and analysis of prognostic factors

Abstract: The aim of this study was to integrate the available data published on Liposarcomas (LPSs) of the oral cavity into an analysis of its clinical features, treatment modalities, and prognostic factors. An electronic search was undertaken in January 2019. The eligibility criteria included publications that had enough clinical and histological information to confirm the diagnosis. Forty‐five publications (104 LPSs) were included. The lesion was more prevalent in males from the fifth to seventh decades of life. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 31 publications
(144 reference statements)
0
26
0
Order By: Relevance
“…Myxoid liposarcoma has a relatively good prognosis, with a five-year survival rate of 80–90%. In liposarcomas of the oral cavity, survival rates are calculated at 66.4% [ 8 ]. There is a high incidence of local recurrence of up to 33% [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Myxoid liposarcoma has a relatively good prognosis, with a five-year survival rate of 80–90%. In liposarcomas of the oral cavity, survival rates are calculated at 66.4% [ 8 ]. There is a high incidence of local recurrence of up to 33% [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nodal metastases are rare with primary liposarcomas of the head and neck region, as well as with any type of primary liposarcoma [ 7 , 11 ]. A systematic review published on primary oral liposarcomas reported a 2% incidence of distal metastases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations